2018
DOI: 10.1021/acs.jpclett.8b03066
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Water at the Electrochemical Interfaces: Electrochemical Behavior of Free Water Versus Coordinating Water

Abstract: The water reduction that produces hydrogen is one key reaction for electrochemical energy storage. While it has been widely studied in traditional aqueous electrolytes for water splitting (electrolyzers), it also plays an important role for batteries. Indeed, the reduction of water at relatively high potential prevents the practical realization of high-voltage aqueous batteries, while water contamination is detrimental for organic battery electrolytes. Nevertheless, recent studies pointed toward the positive e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
119
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 39 publications
7
119
0
Order By: Relevance
“…Organic molecules with strong polarities often contain the elements O, N, or F, whose lone pairs of electrons can be coordinated with Li + , [ 18 ] while organic molecules must have a Brønsted acidity much lower than that of water to form dense SEI layers. Based on the proton theory of acids and bases, the Brønsted acidity of organic compounds should be much lower than that of water in the case of hydrogen evolution, [ 19 ] as if organic molecules with reactive hydrogen atoms coordinate to Li + , both water and organic molecules will contribute to hydrogen evolution at the anode. [ 20 ] After screening potential organic molecules, we finally chose urea, DMSO, and DMF molecules for use in the Li + solvation shell for three reasons: 1) they are strongly polar aprotic solvents, which are miscible with water and have good dissolution ability for salts; 2) their low proton activities intrinsically help to prevent hydrogen evolution; and 3) they contain functional groups that can take part in electrochemical reactions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic molecules with strong polarities often contain the elements O, N, or F, whose lone pairs of electrons can be coordinated with Li + , [ 18 ] while organic molecules must have a Brønsted acidity much lower than that of water to form dense SEI layers. Based on the proton theory of acids and bases, the Brønsted acidity of organic compounds should be much lower than that of water in the case of hydrogen evolution, [ 19 ] as if organic molecules with reactive hydrogen atoms coordinate to Li + , both water and organic molecules will contribute to hydrogen evolution at the anode. [ 20 ] After screening potential organic molecules, we finally chose urea, DMSO, and DMF molecules for use in the Li + solvation shell for three reasons: 1) they are strongly polar aprotic solvents, which are miscible with water and have good dissolution ability for salts; 2) their low proton activities intrinsically help to prevent hydrogen evolution; and 3) they contain functional groups that can take part in electrochemical reactions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the hydrogen evolution reaction (HER, H 2 O + e − = 1/2 H 2 + OH − ) is more likely to take place during battery operation. [ 19 ] By adding urea to the LiClO 4 solutions, we prepared three electrolytes of different concentrations with LiClO 4 ‐H 2 O‐urea ratio of 1‐5‐2, 1‐4‐2, and 1‐3‐2 (referred to as 1‐5‐2 electrolyte, 1‐4‐2 electrolyte, and 1‐3‐2 electrolyte, respectively). On addition of urea, the electrolyte pH values steadily increase, from pH = 4.6 in the normal 5 m LiClO 4 solution to almost pH = 6.8 in the 1‐3‐2 electrolyte, where more neutral solutions suppress hydrolysis more effectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 For example, in batteries it has already been shown that by moving to mixed-solvents, metal dendrite formation can be suppressed 34 and in electrocatalysis, water molecule reactivity can be increased through watersolvent co-ordination bonding. 35 Furthermore, many of the studies that work in a non-aqueous solvent system, be it organic, ionic liquid or deep eutectic solvents are in reality highly likely to be mixed solvent due to the uptake of trace water, which can be difficult to exclude completely. 36 In this work we investigate the electrodeposition of Pd, from its metallo-organic salt (Pd-acetate) in miscible organicaqueous solvents; here water and acetonitrile (MeCN), under organic rich (90% : 10% MeCN : water v/v), water rich (10% : 90% MeCN : water v/v) and equal contributions of both solvent by volume (50% : 50% v/v), conditions.…”
mentioning
confidence: 99%
“…4 Very recent studies, however, suggest that the strong Lewis acidity of Li + promotes the hydrogen evolution reaction (HER) at the anode, especially at high salt concentrations. 5 If the high salt concentrations of WiSEs and WiBS electrolytes do not intrinsically hamper the HER, more attention must be given to the SEI formation and its influence in the overall ESW. Indeed, several homogeneous 6 and heterogeneous 7 Step-wise isothermal thermogravimetric analysis of the WiBS electrolyte.…”
mentioning
confidence: 99%